2010
DOI: 10.3945/jn.109.111450
|View full text |Cite|
|
Sign up to set email alerts
|

Energy Restriction Is Associated with Lower Bone Mineral Density of the Tibia and Femur in Lean but Not Obese Female Rats

Abstract: Energy restriction decreases bone mineral density (BMD), and epidemiological studies suggest that the risk of weight loss-induced bone loss is greater in lean than in heavier individuals. Our goal in this study was to determine how bone density and geometry respond to energy restriction in mature obese rats compared with lean rats. At 6 mo of age, 36 diet-induced obese and lean female Sprague-Dawley rats were allocated to control (CTL; ad libitum; n = 18) and energy-restricted (EnR; 40% restriction; n = 18) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
(83 reference statements)
0
23
1
Order By: Relevance
“…The effect of voluntary running exercise on BMD has been reported to be positive [3,20]. In contrast, the influence of food restriction on BMD has been reported to be negative in sedentary rats [12,14] and in exercising rats [11]. In the present study, we revealed that there were interactions of voluntary running exercise and food restriction on the BMD of the lumbar spine and tibia; the BMD values of the lumbar spine and tibia in the EX-FR group were lower than those in the SED-FR group (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effect of voluntary running exercise on BMD has been reported to be positive [3,20]. In contrast, the influence of food restriction on BMD has been reported to be negative in sedentary rats [12,14] and in exercising rats [11]. In the present study, we revealed that there were interactions of voluntary running exercise and food restriction on the BMD of the lumbar spine and tibia; the BMD values of the lumbar spine and tibia in the EX-FR group were lower than those in the SED-FR group (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported that food restriction in sedentary female rats induces low BMD [12][13][14]. Furthermore, it has been reported that food restriction in female rats undergoing an exercise regimen induced low bone mineral content (BMC) [9,10] and BMD [11].…”
Section: Introductionmentioning
confidence: 98%
“…However at Day 28 the X-ray absorption peak shifted towards the lower grayscale. The PCL-CaSO4 Grayscales values are proportional to the material density (Hawkins et al, 2010). It is postulated that a reduction in material density could be related to the degradation of the 3DP structure as a consequence of resorption time.…”
Section: µ-Ct Analysismentioning
confidence: 99%
“…Reduced body mass due to CR has been shown to decrease BMD (Hawkins et al 2010), which may be explained by mechanisms such as a decreased loading of the bones, less calcium intake from food, or changes in hormonal levels (Hawkins et al 2010). Interestingly, we did not observe any alterations of BMD in the femoral condyles in our CR model.…”
Section: Discussionmentioning
confidence: 50%